2019
DOI: 10.1007/s10100-019-00628-x
|View full text |Cite
|
Sign up to set email alerts
|

Application of hidden Markov models to eye tracking data analysis of visual quality inspection operations

Abstract: Visual inspection is used in many areas due to the potential high costs of inspection error such as injury, fatality, loss of expensive equipment, scrapped items, rework, or failure to procure repeat business. This study presents an application of hidden Markov models (HMM) to fixations' sequences analysis during visual inspection of front panels in a home appliance facility. The eye tracking data are gathered when quality control operators perform their tasks. The results support the difference between expert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…In Rajakumari et al [86], the authors recognized six basic emotions in their works namely anger, fear, happiness, focus, sleep, and disgust by using a Hidden Markov Model (HMM), which is widely used machine learning approach [87][88][89][90][91]. The study of Ulutas et al [92] and Chuk et al [93] presented the applications of HMM to eye-tracking data. They carried out the studies by measuring the distance between sclera and iris which were then used as features to classify the above mentioned six emotions.…”
Section: Distance Between Sclera and Irismentioning
confidence: 99%
“…In Rajakumari et al [86], the authors recognized six basic emotions in their works namely anger, fear, happiness, focus, sleep, and disgust by using a Hidden Markov Model (HMM), which is widely used machine learning approach [87][88][89][90][91]. The study of Ulutas et al [92] and Chuk et al [93] presented the applications of HMM to eye-tracking data. They carried out the studies by measuring the distance between sclera and iris which were then used as features to classify the above mentioned six emotions.…”
Section: Distance Between Sclera and Irismentioning
confidence: 99%
“…Recent research demonstrated that HMM-based approaches may unravel new insights about cognitive functions (e.g., learning, decision making) [ 58 , 59 ]. A HMM allows for the identification of not yet considered commonalities as well as differences between novices and experts during the comprehension of process models, thereby enabling a better support in model comprehension [ 60 ]. All potential findings collected during the three studies can be used to foster process model comprehension, thereby having direct impacts on research and practice (see Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Their dynamics may be modeled by hidden Markov models (cf. [102][103][104][105][106][107][108]), their fuzzy equivalents (see [109][110][111]), or even Markov switching models (cf. [112,113]).…”
Section: Validation Studiesmentioning
confidence: 99%